1988
DOI: 10.3109/00016358809004749
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial systems of human whole saliva in relation to dental caries, cariogenic bacteria, and gingival inflammation in young adults

Abstract: The association of salivary antibody (total IgA, IgG, and IgM and antibodies reactive with Streptococcus mutans) and non-antibody (lysozyme, lactoferrin, salivary peroxidase, myeloperoxidase, hypothiocyanite, thiocyanate) defense factors with oral health (past and present dental caries, gingival bleeding, the number of salivary S. mutans and lactobacilli) were studied in 50 naval recruits. Dental caries was significantly associated with large amounts of S. mutans, lactobacilli, and total salivary immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
3
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 31 publications
5
26
3
1
Order By: Relevance
“…Similar findings in salivary antimicrobial parameters were reported by other investigators [Tenovuo et al, 1986a;Ben-Aryeh et al, 1988;Belazi et al, 1998;Lopez et al, 2003;Mata et al, 2004]. In spite of its perceived antimicrobial properties [Marcott and Levoie, 1998], there is, however, no solid proof of a caries-protective effect of salivary total IgA [Gregory et al, 1986;Gråhn et al, 1988;Marcott and Lavoie, 1998;Hicks et al, 2003], and subjects with total IgA deficiency in saliva do not display higher caries prevalences than healthy subjects [Norhagen Engström et al, 1992;Kirstilä et al, 1994].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar findings in salivary antimicrobial parameters were reported by other investigators [Tenovuo et al, 1986a;Ben-Aryeh et al, 1988;Belazi et al, 1998;Lopez et al, 2003;Mata et al, 2004]. In spite of its perceived antimicrobial properties [Marcott and Levoie, 1998], there is, however, no solid proof of a caries-protective effect of salivary total IgA [Gregory et al, 1986;Gråhn et al, 1988;Marcott and Lavoie, 1998;Hicks et al, 2003], and subjects with total IgA deficiency in saliva do not display higher caries prevalences than healthy subjects [Norhagen Engström et al, 1992;Kirstilä et al, 1994].…”
Section: Discussionsupporting
confidence: 75%
“…Some antimicrobial factors of saliva are considered to be caries protective [Amerongen et al, 2004;Bardow et al, 2005], and may have a beneficial effect on the ecology of dental plaque, but no single factor (except, perhaps, salivary flow rate) is able to affect oral health to a significant degree [Tenovuo et al, 1987;Gråhn et al, 1988;Rudney et al, 1993;Kirstilä et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…No significant correlations were found between levels of any of the antimicrobial agents and caries increments, caries score or gingival index. The only significant correlation that was observed was be tween total protein in stimulated saliva and mean oral hygiene scores as measured by the simplified Greene and Vermillion [1964] oral debris index.These find ings are in agreement with those reported by Grahn et al [1988] except that no correlations were seen in this study between lysozyme and gingival inflammation or immunoglobulins and dental caries. Hence results of this investigation indicate that the prolonged use of a dentifrice containing 0.5% zinc citrate, which has previously been shown to inhibit plaque formation [Jones et al, 1988], does not affect the salivary con centrations of lysozyme, lactoferrin, immunoglobulin A, total protein, nor reduce the activity of salivary peroxidase.…”
supporting
confidence: 83%
“…Many studies have also been under taken over the past two decades to establish correla tions between the constituents of saliva and clinically observed dental health [Twetman et al, 1981]. A re cent study by Grahn et al [1988] on young adults in corporated a review of the variable results previously reported in the literature when the natural antimi crobial systems of human saliva were correlated with dental health parameters, especially caries. Several factors have been indicated as causing these inconsis tencies including age, type of saliva sample taken and analysis method.…”
mentioning
confidence: 99%
“…This can lead to substantial underestimation of peroxidase activity in persons with large amounts of salivary thiocyanate. Assays which eliminate this problem have been devised (Mansson-Rahemtulla et al, 1986), and they are now in common use (Tenovuo et al, 1987;Grahn et al, 1988;Rudney, 1989;Rudney et al, 1991). However, peroxidase activities measured in recent studies may not be fully comparable with those found in earlier studies.…”
Section: (D) Assay Methodsmentioning
confidence: 69%